2008
DOI: 10.1021/cg7012705
|View full text |Cite
|
Sign up to set email alerts
|

Polymorph Selective Growth of Sodium Tetrakis(2-pyridinecarboxylato) Lanthanides and Their Structure Sensitive Properties

Abstract: Four new single crystals of sodium tetrakis(2-pyridinecarboxylato)Ln(III), where Ln is europium and terbium, with general formulas of Na[Ln(C6H4NO2)4]·2H2O were prepared from a reaction of solvent-mediated polymorph selection. All the crystal structures were determined by using temperature-dependent single crystal X-ray diffraction at 100(2) and 298(2) K. No phase transition was observed within this temperature range. Two isostructural compounds, IM (Eu3+ core) and IIIM (Tb3+ core), crystallize in the monocl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…The reported distances of metal-oxygen in Nd, 7,9,10 Sm, 4,7,13 Eu, 6 Tb, 6 Dy, 8 Ho, 4,11 Er 12 complexes in a decreasing atomic radii are 2.460, 2.453, 2.390, 2.390, 2.342, 2.333 and 2.291 Å, respectively. The averaged bond distance of cerium-nitrogen in pyridine ring is 2.756 Å, which is in the range of expected value.…”
Section: Notesmentioning
confidence: 95%
See 3 more Smart Citations
“…The reported distances of metal-oxygen in Nd, 7,9,10 Sm, 4,7,13 Eu, 6 Tb, 6 Dy, 8 Ho, 4,11 Er 12 complexes in a decreasing atomic radii are 2.460, 2.453, 2.390, 2.390, 2.342, 2.333 and 2.291 Å, respectively. The averaged bond distance of cerium-nitrogen in pyridine ring is 2.756 Å, which is in the range of expected value.…”
Section: Notesmentioning
confidence: 95%
“…The averaged bond distance of cerium-nitrogen in pyridine ring is 2.756 Å, which is in the range of expected value. The reported distances of metal-nitrogen in Nd, 7,9,10 Sm, 4,7,13 Eu, 6 Tb, 6 Dy, 8 Ho, 4,11 Er 12 complexes in a decreasing atomic radii are 2.674, 2.674, 2.619, 2.618, 2.520, 2.609, and 2.511 Å, respectively. The results conclude that the bond distances and coordination numbers are relevant with ion size.…”
Section: Notesmentioning
confidence: 96%
See 2 more Smart Citations
“…We have reported that when europium(III) reacted with the α-pyridoin anion in methanol aerobically, metal complex in which europium was coordinated by picolinates (pic) was produced as shown in Figure 1. 10 The complex exhibited bright light-emitting properties when it was irradiated by UV light. We had fully characterized the crystal structure and the light-emitting properties of the europium complex.…”
Section: Introductionmentioning
confidence: 99%